Kronična urtikarija in njen vpliv na kakovost življenja bolnikov - Kramberger, Urška (Farmacevtski vestnik, 2017)
Although chronic urticaria, which is often accom- panied by angioedema, is not a life-threatening condition, it can importantly deteriorate patients' quality of life. In order to explore the importance of different factors impacting the quality of life, questionnaires were prepared and distributed to CU pa tients at the Dermatovenerological Clinic, University Medical Centre Ljubljana and at the Golnik Clinic. We received completely filled in anonymous questionnaires from 38 participants (88%) out of 43 handed out to CU patients. As expected, the majority of them, i.e. 33 (87%), were females. The re sults of our study show a profound impact of the disease on the impairment of patients' quality of life. Angioedema was more common in those suffering from CU for more than 5 years. In this group of patients, the disease had also significantly more negative impacts on their self-perception and selfconfidence. Those affected by more severe forms of CU reported problems with sleeping and the social life. We also found a distinctive influence of stress on the onset, duration and seriousness of CU.
Keywords: anketni vprašalnik; Diagnostika; kakovost življenja; kožne bolezni; kronična utikarija; standard of living; zdravljenje kronične urtikarije